The International Law Perspective of Welfare against Indigenous People in the Omnibus Law on Job Creation - Sulbadana, Sulbadana; Irwansyah, Irwansyah; Tampubolon, Hatta Roma (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Indigenous peoples attach customary rights to themselves, namely rights owned by a legal alliance (such as Lipu, Boya, Ngata, Banua, etc.), where the citizens of the community (the legal alliance) have the right to control the land, the implementation of which is regulated by the head of the guild (the chief/village head concerned). Based on this right, the customary rights of indigenous peoples are basic rights inherent in the life of these people that are not a gift from the state. It is the same with the basic rights inherent in every human being, for example the right to life, which is not a gift of the state.Purposes of the Research: Review and analyze international law relating to the welfare of Indigenous Peoples in the Omnibus Law on Job Creation.Methods of the Research: Its legal position in the Job Creation Law which has the character of omnibus law through juridical studies with a philosophical approach, conceptual approach, and a statutory approach.Results of the Research: The right of indigenous peoples which is essentially the right to the value of justice and welfare value to the use of natural resources of indigenous peoples who not yet the maximum expected in the job creation law can provide justice and welfare for indigenous peoples over exploited customary territories.